Loose Network, Dense Network, and The Shift of Joseigo Usage - Eva Krishna Adnyani, Kadek (e-Journal of Linguistics; Vol 12 No 1 (2018): eJL-January, 2018)
This research aims to analyze the relationship between social network (including loose network and dense network) and the shift in the use of joseigo by Japanese women in Ubud, Bali. This research uses qualitative research method. Japanese women who settled in Ubud were used as the subject of this research. The results showed that involvement in loose social networks has more shifting in using joseigo by Japanese women in Ubud compared to the involvement in dense social networks. The involvement of subject using joseigo in a dense social networks relatively has higher frequencies as well as more varied. On the contrary, in loose social networks, the involvement of subject using joseigo has  lower  frequency and less variable. Loose social networks make individuals to be more open with changes.